PENGARUH PERSEPSI GENERASI LANGGAS TENTANG KUALITAS DAN INOVASI BATIK TERHADAP KEPUTUSAN PEMBELIAN DI ERA DIGITAL - Tisia Priskila (Journal of Business & Applied Management, 2018)
Indonesia is experiencing serious problems in the era of globalization. Since the era of freetrade, many imported products have flooded the national marketplace. Lack of domestic products‟competition on its own country make business actors in Indonesia must understand about purchasingdecision of millennial generations that will become the next generations of the nation. Their purchasingdecision depends on the product quality perception and they want products that suit with their style.Millennial generations outreach through social media marketing is believed to be necessary to influencetheir purchasing decisions. The research objectives are to know the effect of the perception of modernBatik product quality and product innovation on purchasing decisions with social media marketing as amoderator variable. The analysis method used is Partial Least Square (PLS) with sample of 100respondents. The research results show that the millennial generations‟ purchasing decisions are affectedby their perception of product quality and innovation. The perception of product quality and purchasingdecisions are weakened by social media marketing. The perception of product innovation and purchasingdecisions are not affected by social media marketing as moderator variable.Keywords: perception, quality, innovation, marketing, purchasing decision